If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + 3) = 11 Reorder the terms: x(3 + x) = 11 (3 * x + x * x) = 11 (3x + x2) = 11 Solving 3x + x2 = 11 Solving for variable 'x'. Reorder the terms: -11 + 3x + x2 = 11 + -11 Combine like terms: 11 + -11 = 0 -11 + 3x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '11' to each side of the equation. -11 + 3x + 11 + x2 = 0 + 11 Reorder the terms: -11 + 11 + 3x + x2 = 0 + 11 Combine like terms: -11 + 11 = 0 0 + 3x + x2 = 0 + 11 3x + x2 = 0 + 11 Combine like terms: 0 + 11 = 11 3x + x2 = 11 The x term is 3x. Take half its coefficient (1.5). Square it (2.25) and add it to both sides. Add '2.25' to each side of the equation. 3x + 2.25 + x2 = 11 + 2.25 Reorder the terms: 2.25 + 3x + x2 = 11 + 2.25 Combine like terms: 11 + 2.25 = 13.25 2.25 + 3x + x2 = 13.25 Factor a perfect square on the left side: (x + 1.5)(x + 1.5) = 13.25 Calculate the square root of the right side: 3.640054945 Break this problem into two subproblems by setting (x + 1.5) equal to 3.640054945 and -3.640054945.Subproblem 1
x + 1.5 = 3.640054945 Simplifying x + 1.5 = 3.640054945 Reorder the terms: 1.5 + x = 3.640054945 Solving 1.5 + x = 3.640054945 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.5' to each side of the equation. 1.5 + -1.5 + x = 3.640054945 + -1.5 Combine like terms: 1.5 + -1.5 = 0.0 0.0 + x = 3.640054945 + -1.5 x = 3.640054945 + -1.5 Combine like terms: 3.640054945 + -1.5 = 2.140054945 x = 2.140054945 Simplifying x = 2.140054945Subproblem 2
x + 1.5 = -3.640054945 Simplifying x + 1.5 = -3.640054945 Reorder the terms: 1.5 + x = -3.640054945 Solving 1.5 + x = -3.640054945 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.5' to each side of the equation. 1.5 + -1.5 + x = -3.640054945 + -1.5 Combine like terms: 1.5 + -1.5 = 0.0 0.0 + x = -3.640054945 + -1.5 x = -3.640054945 + -1.5 Combine like terms: -3.640054945 + -1.5 = -5.140054945 x = -5.140054945 Simplifying x = -5.140054945Solution
The solution to the problem is based on the solutions from the subproblems. x = {2.140054945, -5.140054945}
| 9-4m=2m-3 | | Y=2(0+3)(0-4) | | 4y-23=10+y | | 23+13x-15+5x-27x= | | 14000V=-2000t+20000 | | 5(9a)= | | 14000V=-2000+20000 | | -10x+14-8x+9= | | 3x-4(1-2x)=2x-(x+1) | | 2(a-b)= | | 3.7(-83x+-3)=3.7(7x+-30) | | (2x-1/2)^2=9/4 | | X+2x+4x+2=37 | | (13-6)x(12-3)+16= | | 3a^2+25+42=0 | | 9n=6 | | -49=.7y | | 2[5(4-1)]= | | x-4=169 | | t^2-19t+10=0 | | x^2y^2-2y=0 | | in(2x)-in(3x+2)=1 | | -8(w-3)=9w+41 | | (7x-9)(9x+9)=0 | | (49-12)/3 | | (2x-7)(9x+8)=0 | | 17=85 | | 17Xa=85 | | x+25=51 | | 3p^3+12p=0 | | 4(p+17.00)=53.50 | | 4p+17.00=53.00 |